Polymorphic Variants of TNFR2 Gene in Schizophrenia and Its Interaction with -308G/A TNF-α Gene Polymorphism - Renata Suchanek-Raif; Paweł Raif; Małgorzata Kowalczyk; Monika Paul-Samojedny; Krzysztof Kucia; Wojciech Merk; Jan Kowalski (Mediators of Inflammation)
Aim. Many data showed a role of inflammation and dysfunction of immune system as important factors in the risk of schizophrenia. The TNFR2 receptor is a molecule that adapts to both areas. Tumor necrosis factor receptor 2 (TNFR2) is a receptor for the TNF-α cytokine which is a strong candidate gene for schizophrenia. The serum level of TNFR2 was significantly increased in schizophrenia and associated with more severe symptoms of schizophrenia. Methods. We examined the association of the three single nucleotide polymorphisms (rs3397, rs1061622, and rs1061624) in TNFR2 gene with a predisposition to and psychopathology of paranoid schizophrenia in Caucasian population. The psychopathology was measured by a five-factor model of the PANSS scale. We also assessed a haplotype analysis with the -308G/A of TNF-α gene. Results. Our case-control study (401 patients and 657 controls) revealed that the genetic variants of rs3397, rs1061622, and rs1061624 in the TNFR2 gene are associated with a higher risk of developing schizophrenia and more severe course in men. However, the genotypes with polymorphic allele for rs3397 SNP are protective for women. The rs1061624 SNP might modulate the appearance of the disease in relatives of people with schizophrenia. The CTGG haplotype build with tested SNPs of TNFR2 and SNP -308G/A of TNF-α has an association with a risk of schizophrenia in Caucasian population depending on sex. Our finding is especially true for the paranoid subtypes of schizophrenia.